2021
DOI: 10.1177/0194599821993813
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of the Incudomalleolar Joint in Cases of “Indeterminate” Presbycusis

Abstract: Age-related hearing loss (presbycusis) is a prevalent condition attributed primarily to inner ear dysfunction. Little is known about age-related changes in the ossicular joints or their contribution to presbycusis. Herein, we performed a histopathologic analysis of the incudomalleolar joint (IMJ) in specimens from the National Temporal Bone Registry with audiometrically confirmed presbycusis but without histologically observed sensory, neural, strial, or mixed features. Seventeen “indeterminate” presbycusis (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Of note, in a recent study of 153 IMJ specimens, Dobrev et al demonstrated an age‐related increase in the IMJ space with a methodologically similar approach to the one adopted in the current study 29 . This age‐related increase in IMJ width is in keeping with key findings from this study as well as with previous work from our group 30 . However, a key difference between our present work and the analysis performed by Dobrev et al is the lack of comparison of classic histopathologic subtypes of presbycusis.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, in a recent study of 153 IMJ specimens, Dobrev et al demonstrated an age‐related increase in the IMJ space with a methodologically similar approach to the one adopted in the current study 29 . This age‐related increase in IMJ width is in keeping with key findings from this study as well as with previous work from our group 30 . However, a key difference between our present work and the analysis performed by Dobrev et al is the lack of comparison of classic histopathologic subtypes of presbycusis.…”
Section: Discussionsupporting
confidence: 91%
“…There is a limited number of reports that conducted analyses of the microstructure of the middle ear, particularly focusing on ossicular joints. Roychowdhury (2021) et al reported that in cases of presbycusis, 13 the joint discus distance and the bone‐line distance were significantly longer compared to control cases. In the context of a previous study discussing “age‐related hearing loss” in a broad sense, 13 age‐related changes were characterized by an elongation of both the bone‐line distance and joint discus distance.…”
Section: Discussionmentioning
confidence: 99%
“…Roychowdhury (2021) et al reported that in cases of presbycusis, 13 the joint discus distance and the bone‐line distance were significantly longer compared to control cases. In the context of a previous study discussing “age‐related hearing loss” in a broad sense, 13 age‐related changes were characterized by an elongation of both the bone‐line distance and joint discus distance. However, within the Control groups of this study, there were no significant differences observed in either the bone‐line distance or joint discus distance between younger and older groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations